PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. WIN ACCES TELECOMMUNICATION PALEMBANG DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Patri Hasni; Djatmiko Noviantoro; Dian Septianti (Jurnal Aplikasi Manajemen dan Bisnis, 2020)
This research aims to find out how much leadership impact on employee performance in PT. Win Acces Telecommunication Palembang with the satisfaction of working as a variable intervening. This research uses primary and secondary data. The population of the research is all employees of PT. Win Acces Telecommunication Palembang, sampling techniques using census samples with a sample number of 46 respondents. Data analysis techniques are quantitative by using linear regression and pathway analysis. The results showed that the leadership and work satisfaction of a partial and simultaneous effect on performance with the significance of 0.000. In a direct, leadership impact on performance is 41% while the impact of leadership on performance through the work of the intervening variable is 13%. The research also proves that job satisfaction is not proven as an intervening variable.